The Leicester cerebral haemodynamics database: normative values and the influence of age and sex. (11th August 2016) - Patel, Nikil; Panerai, Ronney B; Haunton, Victoria; Katsogridakis, Emmanuel; Saeed, Nazia P; Salinet, Angela; Brodie, Fiona; Syed, Nazia; D'Sa, Schnell; Robinson, Thompson G
Abstract: Normative values of physiological parameters hold significance in modern day clinical decision-making. Lack of such normative values has been a major hurdle in the translation of research into clinical practice. A large database containing uniform recordings was constructed to allow more robust estimates of normative ranges and also assess the influence of age and sex. Doppler recordings were performed on healthy volunteers in the same laboratory, using similar protocols and equipment. Beat-to-beat blood pressure, heart-rate, electrocardiogram, and end-tidal CO2 were measured continuously. Bilateral insonation of the middle cerebral arteries (MCAs) was performed using TCD following a 15 min stabilisation, and a 5 min baseline recording. Good quality Doppler recordings for both MCAs were obtained in 129 participants (57 female) with a median age of 57 years (range 20–82). Age was found to influence baseline haemodynamic and transfer function analysis parameters. Cerebral blood flow velocity and critical closing pressure were the only sex-related differences found, which was significantly higher in females than males. Normative values for cerebral haemodynamic parameters have been defined in a large, healthy population. Such age/sex-defined normal values can be used to reduce the burden of collecting additional control data in future studies, as well as to identify disease-associated changes.